The factor proportions theory of international trade empirical results from the United States and the Philippines - Lassiter, Gregory C.; Sisler, Daniel G. (The Philippine Review of Business and Economics, 1984)
This paper tests empirically whether the factor proportions or Hecksher-Ohlin theory is applicable to two countries with highly contrasting factor endowments - the United States and the Philippines. A multi-factor model is presented which includes measures of skilled labor, technology and natural resources along with capital and labor; and incorporates a measure of net export performance that overcomes weaknesses in previously used measures. It was hoped that empirical tests of this more elaborate trade model might reconcile the paradoxical tests results of the more simplistic two-factor models. The findings however, provide few definitive guidelines in the development of a more refined empirical test.